Cancer - Naff, Clay Farris (Detroit : Greenhaven Press, 2008)
Presents essays discussing cancer, including causes, prevention, detection, treatment, and cures.
1. Skin cancer and sunlight -- 2. Risk factors for lung cancer -- 3. The role of diet and hormones in breast cancer -- 4. Pancreatic cancer and its many symptoms -- 5. Ovarian cancer and the problem of diagnosis -- 6. Cancer of the lymphatic system -- 7. Chemotherapy -- 8. Radiation therapy -- 9. Treating kids with cancer -- 10. New treatments for breast cancer -- 11. Attacking cancer with vitamin therapy -- 12. Prostate cancer and its treatments -- 13. Unconventional cancer treatments -- 14. Losing a womb, gaining a cause -- 15. A parent's perspective -- 16. Finding faith while cancer spreads -- 17. Surviving non-Hodgkins lymphoma -- 18. An Asian American faces breast cancer -- 19. Blogging a battle with cancer
Includes bibliographical references and index
Keywords: Cancer -- Juvenile literature; Neoplasms -- diagnosis; Neoplasms